Sustainable Combustion Systems and Their Impact - Rahman, S. M. Ashrafur; Fattah, Islam Md Rizwanul (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
As the world enters the third decade of the 21st century, a shift in global energy demand and use is anticipated. The transportation industry is one of the largest energy users, with major environmental consequences. Additionally, with the most ambitious electric vehicle predictions, the bulk of cars sold in 2040 will still have internal combustion engines. As a result, we must continue to explore all options for reducing IC engine emissions, as well as pathways to reduce potential vehicle CO2 emissions. Hydrogen, on the other hand, which can be used in both internal combustion engines and fuel cells, is seen as one of the future's most important energy vectors. In terms of production, storage, and application, this technology still faces several challenges. This Special Issue features original research papers, as well as important review articles on current issues relating to laboratory research and in-vehicle test results on different renewable combustion strategies that seek to reduce environmental impact.